Preserving Continuity of Behavioral Health Clinical Care to Patients Using Mobile Devices. - Little, Jeanette; Schmeltz, Amanda; Cooper, Mabel; Waldrop, Tabitha; Yarvis, Jeffrey S; Pruitt, Larry; Dondanville, Katy (Military Medicine)
Introduction: The current model for treating behavioral health patients requires that providers and patients be in the same location for appointments. However, deploying warfighters present a challenge to this current model. Recent advances in technology make telehealth or virtual visits a viable option to replace the current model. This project leveraged mobile technology to see if performing tele-behavioral health visits presented a viable option to the current in-person model for future deployed warfighters. At the time of this publication, the authors note the current pandemic lends all the more urgency to the need for enhancing our video communication platforms for remote monitoring with the Military Health System.Materials and Methods: The research team assessed existing Internet protocol-based desktop teleconferencing solutions, generically known as a Web Real-Time Communications (WebRTC) system, for establishing a secure connection to a Service Members personal mobile device outside of the Department of Defense (DoD) network. Of the five existing WebRTC systems evaluated, only the backbone component to the existing Defense Information Systems Agency Global Video Services (DISA GVS) known as Vidyo, was suitable to meet DoD security requirements and still connect with both major operating systems (OS) on mobile devices. An existing DoD program of record mobile application, mCare, was integrated with Vidyo desktop technologies to form what the research team called "Mobile Connect."Results: Deployment of the Mobile Connect product yielded distinct differences and high levels or variability between the .osd.mil and the army.mil network connections over time. These network differences impacted quality of service solution where Mobile Connect could not be used to provide care between the .mil and patient's personal mobile devices from a osd.mil domain connection. The current DoD WebRTC systems offer potential solutions but presently cannot connect with personal mobile devices in their current configurations. Additionally, any WebRTC system used by the DoD for future connections to personal mobile device must leverage commercial Single Socket Layer certificates (e.g., not DoD issued), or the communications with the mobile device will fail as a result of an authentication error.Conclusion: It is technically feasible to provide desktop Video Tele-Conference capabilities from a .mil computer to a personal mobile device without compromising DoD security and information assurance requirements using future WebRTC systems. Approved ports, protocols, and system settings must be configured to accept both inbound and outbound, encrypted traffic to/from personal mobile devices to maintain consistent quality of service with all DoD networks. Of the current DoD WebRTC options, working with the DISA GVS Program Manager to expand services to support commercial mobile devices has the highest probability of future success.